METHOD OF IMPULSE IMPREGNATION OF TIMBER FOR BUILDING STRUCTURES (Collection of scientific works «Modern structures of metal and wood», 2024)
The article discusses the effectiveness of the impulse method of timber impregnation to improve its operational properties when used in building structures. A detailed analysis of modern timber  impregnation  methods  is  presented,  in  particular,  the  traditional  static  and  the  proposed impulse methods. The main advantages of impulse impregnation technology are defined, such as increasing  the  durability  and  fire  resistance  of  wood,  as  well  as  improving  its  physical  and mechanical properties, depending on the type of impregnation composition used. In the course of the study, an experimental comparison of both methods was carried out, the results of which confirm the  high  efficiency  of  the  pulsed  infiltration  method.  The  materials  and  methods  used  for  the experiments are described, including wood characterization and the pulsed impregnation process. A detailed description of the proposed technology  of impulse impregnation of wood is  given. The results of the research can be used to improve wood processing methods and increase its operational properties in building structures, which contributes to more efficient and widespread use of timber as a building material. The purpose of this study is to develop and optimize the method of impulse impregnation of wood to improve its properties when used in building structures. The research is aimed at identifying the effectiveness of the impulse method in comparison with the static method of timber impregnation. In the conducted research, a detailed description of an effective method of wood modification for building structures, which is implemented using the technology of impulse impregnation  of  wood  with  technological  compositions,  was  proposed  and  performed.  This technology allows you to intensify the wood processing process, increase the penetration depth of the impregnating liquid into the pores of the wood and ensure a more even distribution of the liquid in the wood structure. This is important for increasing the durability and operational properties of wooden structures depending on the type of impregnation composition (for example, fire resistance, biological resistance, strength, hydrophobicity). The obtained experimental data prove the positive effect of the impulse component of pressure on increasing the depth and achieving homogeneity of penetration of the impregnating liquid into the capillary-porous structure of wood. Keywords:  wooden  structures;  building  materials;  fire  protection;  biological  protection; impregnation; saturation; capillary-porous body.